Hubungan Antara Self-Efficacy dengan Kecemasan Komunikasi dalam Mempresentasikan Tugas di Depan Kelas - Deviyanthi, Ni Made Ferra Sarah; Widiasavitri, Putu Nugrahaeni (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Psychology student is required to have a good communication skills in situations of personal and public. One of the competencies that must be owned by bachelor of psychology are skilled in interpersonal communication and have an ability to communicate with each other. Handling the anxiety experienced by individuals may differ between one individual with another individual depends on an individual assessment of the capabilities that called self-efficacy (Sarafino, 1994).Self-efficacy is a believefrom individual against all aspects of the advantages who aims to reach an achievement.A total of 175 students in Udayana University and Dhyana Pura University are still actively follow lectures and do an individual presentations in front of the class became a subject in this correlational quantitative study. The sampling technique used was simple random samplingData were processed using Pearson Product Moment analysis, simple linear regression, independent sample t-test, and one-way ANOVA analysis. Statistical analysis show, there is significant correlation between self-efficacy and communication apprehensionin order to do presentation in front of class (r = -0,725; p = 0,000). The coefficient of determination obtained for 0,540 which means that 54 % of the variance that occurs in the communication apprehension in order to do a presentationin front of the class variable can be explained by the variance in self-efficacy variable. T test and F test analysis found that the mean scores for communication apprehension in order to do a presentationin front of the class did not differ significantly when assessed from the gender (T = 1,389; p = 0,167) and there are differences in communication apprehension in presenting the task in front of the class when examined from many individual presentation experience (F = 15,848 ; p = 0,000).Keywords: Self-efficacy, communication apprehensionwhen presenting the task in front of the class, students of Psychology.